Serum Malondialdehyde is Associated with Non-Alcoholic Fatty Liver and Related Liver Damage Differentially in Men and Women - Shira Zelber-Sagi; Dana Ivancovsky-Wajcman; Naomi Fliss-Isakov; Michal Hahn; Muriel Webb; Oren Shibolet; Revital Kariv; Oren Tirosh (MDPI AG, 2020)
Background: Non-alcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH) are associated with increased oxidative stress and lipid peroxidation, but large studies are lacking. The aim was to test the association of malondialdehyde (MDA), as a marker of oxidative damage of lipids, with NAFLD and liver damage markers, and to test the association between dietary vitamins E and C intake and MDA levels. Methods: A cross-sectional study was carried out among subjects who underwent blood tests including FibroMax for non-invasive assessment of NASH and fibrosis. MDA was evaluated by reaction with Thiobarbituric acid and HPLC-fluorescence detection method. NAFLD was diagnosed by abdominal ultrasound. Findings: MDA measurements were available for 394 subjects. In multivariate analysis, the odds for NAFLD were higher with the rise of MDA levels in a dose-response manner, adjusting for age, gender, BMI, and lifestyle factors. Only among men, higher serum MDA was associated of higher odds for NAFLD and NASH and/or fibrosis (OR = 2.59, 95% CI 1.33-5.07, P = 0.005; OR = 2.04, 1.02-4.06, P = 0.043, respectively). Higher vitamin E intake was associated with lower odds of high serum MDA level (OR = 0.28 95% CI 0.13-0.62, P = 0.002). In conclusion, serum MDA is associated with NAFLD and markers of NASH or fibrosis among men. Dietary vitamin E may be protective among women.